PENGEMBANGAN MODUL PEMBELAJARAN SEJARAH BERBASIS PERISTIWA FRONT LANKAN UNTUK MENINGKATKAN NASIONALISME SISWA DI SMA NEGERI PULAU RIMAU - Satria, Nusiandi Embo; Djono, D.; Agung S., leo (HISTORIKA, 2018)
Background: Research development aims to: (1) described teaching history in senior high school district Pulau Rimau; (2) described the development of material based history of Peristiwa Front Langkan to improve people nationalism; (3) described the effectiveness of material based history the front ledge to improve people nationalism students.  Methods: Research conducted is research development (Research and Development) using methods of Borg and Gall .The method includes: (1) the study introduction , namely the literature study, field studies, and findings teaching needs; (2) developmental stage covering the prototype design, validation expert, the trial one by one, and trial to more participants; (3) the step of experiment the effectiveness of covering test whether material and feasibility history.  Conclusion: The research results show that: (1) teaching history still focused on one source the textbook without any additional or other sources a supporting, the curriculum is using KTSP curriculum, teachers have not have sufficient knowledge about the development of teaching materials; (2) The teaching materials developed with follow a procedure the development of which adapted to a syllabus, validation three experts who put a value the average score 4 for a category ?good?;  trial one by one done on five students and fifteen students, the revision related the literature and grammar; the results of the tryouts broad shows differences in average between class control and class experiment where class experiment more better in terms of achievement and nasioanlisme; (3) the implementation of teaching materials history based Peristiwa Front Langkan to improve nasioanlism proven effective, proven from the acquisition value post-test on class control and experiment to aspects level of achievement with significant 0,000 < 0,025 and than nasionalism aspect with significant 0,000 < 0,025. Shows that Ho rejected which means there is a difference in positive and significant .